2009
DOI: 10.1080/10942910802103028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Defatted Maize Germ Addition on the Functional and Textural Properties Of Wheat Flour

Abstract: The objective of this study was to assess functional properties of wheat flour blends with defatted maize germ flour (DMGF), a byproduct of the corn oil industry, at 5-25% levels. The bulk density, oil, and water absorption capacities, emulsion/foaming capacity and stability, objective color, least gelation concentration, and rheological properties (apparent viscosity and dough compression) were determined in control and flour blends. With DMGF addition, bulk density and foaming capacity decreased from 0.62 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 31 publications
4
55
3
1
Order By: Relevance
“…It was observed that gelation generally started at !8 g/100 ml concentration, with complete gelation observed at !12 g/100 ml for all the bean flours. Our results are similar to those reported by Siddiq et al (2009) for all-purpose wheat flour, which had a least gelation concentration of !12 g/100 ml.…”
Section: Least Gelation Concentrationsupporting
confidence: 94%
See 2 more Smart Citations
“…It was observed that gelation generally started at !8 g/100 ml concentration, with complete gelation observed at !12 g/100 ml for all the bean flours. Our results are similar to those reported by Siddiq et al (2009) for all-purpose wheat flour, which had a least gelation concentration of !12 g/100 ml.…”
Section: Least Gelation Concentrationsupporting
confidence: 94%
“…Bulk density values for bean flours were somewhat similar to that of all-purpose wheat flour with a value of 0.62 g/ml (Siddiq, Nasir, Ravi, Dolan, & Butt, 2009). …”
Section: Bulk Density Water and Oil Absorption Capacitiesmentioning
confidence: 86%
See 1 more Smart Citation
“…The WAI determines the absorption and retention of water and its effect on various processing conditions (Siddiq, Nasir, Ravi, Dolan, & Butt, 2009;Siddiq, Ravi, Harte, & Dolan, 2010). The navy bean EXT flour had significantly higher WAI as compared to raw or STC bean flours, while the pinto bean EXT flour's WAI was different from raw bean flour only (Table 1).…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 98%
“…Furthermore, inulin based functional products have good acceptance in the international markets, these products offer additional benefits in terms of natural prebiotic, dietary fiber, texture modifier, fat or sugar replacer, and stabilizer [8,9]. Functional and pasting properties are necessary to evaluate and possibly assist to predict how new nutrient may behave in specific systems, in addition to demonstrate whether or not such nutrient can be used to stimulate or replace convectional nutrient [10,11]. The aim of this work was to assess the effect of sweet potato flour (SPF), glutinous rice flour (GRF), button mushroom powder (BMP) and inulin on chemical, functional, pasting and syneresis characteristics of enriched composite gluten-free flour, as well as its suitability for baking process.…”
Section: Introductionmentioning
confidence: 99%